Leadership in Pediatric Surgery from a Trainee's Perspective - Zimmer, Julia (European Journal of Pediatric Surgery, 2017)
Role models are fundamental for anyone entering the field of medicine. Proper leadership is especially essential in surgical subspecialties to guide young doctors through their training, ensure surgical experience and skill development, and teach the values of professional and ethical behavior and team management. In the complex field of pediatric surgery, which is composed of a unique patient clientele and age-dependent conditions, specialization, experience, and a strong executive are vital for patient care. Leaders in pediatric surgery are required to find a suitable balance between guidance and controlling a trainee's actions to ensure correct medical and surgical treatment and provide young doctors with the opportunity to grow and gain independent experience. When teaching the present generation of trainees, current leaders need to consider the specific characteristics of the so-called “Millennials” to avoid tension and frustration due to generation diversity. This article aims to assess leadership qualities, character traits, challenges, and expectations in pediatric surgery from a trainee's perspective.
Keywords: leadership; values; pediatric surgery; training; nontechnical skills; Millennials